Smart parking system with real-time parking lot status monitoring using Internet of Things (IoT) and Radio Frequency Identification (RFID) - Tan, Hong Zheng (2025)

(untitled)
The ever-growing number of vehicles in urban areas has significantly intensified the challenge of finding available parking spaces, leading to increased frustration for drivers and contributing to environmental pollution due to prolonged vehicle idling and unnecessary driving. Real-time updates and efficient space utilization are rare features of most parking management systems on the market today. Apart from this, visibility is usually limited, especially in large parking lots, and the signs can be unclear or difficult to read, which causes drivers to have no idea where the available parking spots are. This project presents a Smart Parking System using IoT and RFID Technology designed to address these issues by providing a real-time parking lot status monitoring solution. The system integrates various hardware components, including eight IR sensors to detect vehicle presence at the parking slots, two servo motors for gate control, two ESP32 microcontrollers, two RFID readers with tags, an LCD display for showing parking status and time, an OLED display for showing RFID scanning messages, and a buzzer for audio feedback. Additionally, two IR sensors monitor vehicle presence at each of the gates. Besides that, custom developed HTML-PHP integrated web pages enable public users to view the status of each parking slot in realtime, whether it is “AVAILABLE”, “OCCUPIED”, or “RESERVED” and then access features like sign-up, login, top-up, and reservation, which allow the users to reserve a parking slot for a particular time before arriving. The user information, RFID scanning timestamps, reservation user and time, and status of each parking slot are stored in a MySQL database. Users can obtain parking information on the web page using their mobile devices by scanning a QR code or by visiting the provided URL link and logging into their registered accounts. The system operates by detecting vehicles at the entrance, verifying RFID UID with database, and managing gate operations based on slot availability and account balance. Furthermore, a ESP32-CAM is used to capture vehicle images at the gate entrance when the IR sensor detects movement and save them to Google Drive. The performance of the system will then be assessed based on its accuracy. Based on the results, the system prototype achieved 100 % accuracy. When compared to other proposed Smart Parking Systems, it is clear that this method is more cost-effective and reliable. This system aims to reduce parking-related frustrations and environmental impact to enhance overall urban mobility and sustainability.